2021
DOI: 10.1111/odi.13779
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis is a factor associated with dyslipidemia

Abstract: Objective To investigate the association between the severity of periodontitis (exposure) and dyslipidemia (outcome). Methods This was a cross‐sectional study of users of public health services. Periodontitis was defined using the Center for Disease Prevention and Control and the American Academy of Periodontology criteria. Lipid evaluation used data on systemic biomarkers. Dyslipidemia diagnosis was based on the Guidelines of total cardiovascular risk of the World Health Organization. Weight, height, waist ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
(90 reference statements)
0
13
0
Order By: Relevance
“…The more refined plant foods do not stimulate saliva flow so efficiently and do not ensure self-cleaning as their unrefined counterparts, which worsen buffering capacity and the remineralisation of enamel and support dental plaque accumulation [ 1 , 2 , 3 , 4 ]. With the development of modern healthcare and access to various foods, periodontal diseases related to vitamin C deficiency are almost forgotten, but the ineffective removal of dental plaque in association with chronic stress, inveterate smoking, diabetes, dyslipidemia, etc., may result in periodontitis, which affects a large part of the population worldwide [ 2 , 5 , 6 , 7 , 8 ]. Rising life expectancy generates other problems such as tissue degeneration as well as neoplasms and their treatment, which may result in hyposalivation, immunodeficiency or malnutrition with subsequent oral diseases [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The more refined plant foods do not stimulate saliva flow so efficiently and do not ensure self-cleaning as their unrefined counterparts, which worsen buffering capacity and the remineralisation of enamel and support dental plaque accumulation [ 1 , 2 , 3 , 4 ]. With the development of modern healthcare and access to various foods, periodontal diseases related to vitamin C deficiency are almost forgotten, but the ineffective removal of dental plaque in association with chronic stress, inveterate smoking, diabetes, dyslipidemia, etc., may result in periodontitis, which affects a large part of the population worldwide [ 2 , 5 , 6 , 7 , 8 ]. Rising life expectancy generates other problems such as tissue degeneration as well as neoplasms and their treatment, which may result in hyposalivation, immunodeficiency or malnutrition with subsequent oral diseases [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…91,92 In two recent crosssectional studies, the same group of authors found a positive relationship between periodontitis and the triglyceride/high density lipoprotein cholesterol ratio ≥2.3 (odds ratio 1.47) and a positive association between moderate and severe periodontitis and dyslipidemia, specifically 30% and 16% higher, respectively, than in periodontally healthy patients. 93,94 TA B L E 2 Diabetes and periodontitis comorbidities…”
Section: Dyslipidemiamentioning
confidence: 99%
“…Hyperlipidemic individuals manifest advanced periodontal inflammation and tissue destruction compared to normolipidemic subjects [ 185 ]. In the meantime, periodontitis alters the serum lipid profile in a disease severity-dependent manner [ 253 ] and periodontal therapy helps improve the profile of blood lipids [ 254 ]. Nevertheless, these epidemiological studies could not support the cause–effect relationship between hyperlipidemia and periodontitis due to the limitations of cross-sectional studies.…”
Section: Metabolic Disorders Of Energy Substratesmentioning
confidence: 99%